Representing mental disorders with virtual reality applications: Designing for multimodality and complex participation - Bakk, Ágnes Karolina (Frontiers in Virtual Reality, 2023)
In this paper, I will present various strategies adopted by creators of artistic interactive VR experiences to represent mental health problems and their contexts. The strategies can foster dialogues about these problems, as they present their complexity by embedding them into various narrative and non-narrative elements. When discussing the representational complexity of these works, I emphasize the design strategies that tackle stereotypes and their ethical representations which create a specific type of suspense for the experiencer in order to bypass the representation of suffering that documentary VR works often use. These productions approach mental health issues as dynamic systems, and they represent them through linearity or non-linearity (see Stepney 2018) This approach offers limited agency to the interactor, in the sense that the user has a sense of embodiment (Kilteni et al. 2012) and is scripted as an interactor in specific cases (Murray 1997). In this paper I will argue that the VR medium’s characteristic of expressing non-linearity via its multimodality (see Elleström 2019) and sense of embodiment makes it suitable for such productions.